Media Sosial Tiktok Sebagai Alat Komunikasi Digital Layanan Transpakuan Bogor - Muhammad Avicenna; Sutisna Riyanto; Erna Ernawati (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The rapid development of digital technology has encouraged public institutions to adapt their communication strategies to social media platforms. This study aims to analyze the digital communication strategy of Perumda Transpakuan Bogor through TikTok as a medium for public service communication. Using a descriptive qualitative approach, data were collected through observation of the official TikTok account, in-depth interviews with the Public Relations Division, and documentation. The findings show that Perumda Transpakuan Bogor applies three main pillars in its TikTok communication strategy: setting communication objectives, developing a light and informative communication style, and maintaining content consistency through a monthly content plan. The role of the Social Media Specialist is central in managing production stages from pre-production to post-publication by aligning creative trends with institutional messages. The results also reveal that TikTok effectively increases public awareness and engagement through interactive, educational, and entertaining content. This research implies that strengthening digital communication capacity and continuous evaluation of media strategies are essential for improving public service innovation and institutional credibility in the digital era.